2018
DOI: 10.4038/sljid.v8i2.8216
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on Naegleria species in water bodies of Kurunegala district, Sri Lanka

Abstract: Introduction and Objective:Species belonging to the genus Naegleria are free-living ubiquitous protozoa. They have been isolated from most regions of the world. N. fowleri causes an acute, fulminant and rapidly fatal infection involving the central nervous system (CNS) in humans. It is known as primary amoebic meningoencephalitis (PAM). Infection is generally acquired while swimming, diving and total submersion for bathing in freshwater-lakes and ponds. Many inland fresh water bodies are present in Sri Lanka. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…However, there was no statistical significance in the reported differences (p>0.05). A previous study conducted in Sri Lanka identified Naegleria thrive more significantly in surface water than in deep-water [ 39 ]. Two different studies conducted in the United States of America recorded a higher prevalence rate of Naegleria in surface water [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no statistical significance in the reported differences (p>0.05). A previous study conducted in Sri Lanka identified Naegleria thrive more significantly in surface water than in deep-water [ 39 ]. Two different studies conducted in the United States of America recorded a higher prevalence rate of Naegleria in surface water [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%